Pemberdayaan kemandirian keluarga melalui inovasi asuhan keperawatan gigi dalam meningkatkan status kesehatan gigi anak di Kota Banda Aceh (Empowerment of family independence through innovation of dental nursing care in improving dental health status in Banda Aceh) - Reca, R; Salfiyadi, Teuku Salfiyadi; Nuraskin, Cut Aja; Mufizarni, M (Universitas Syiah Kuala, 2022)
Family dental and oral health care is an effective approach to improving dental health. Family dental care with a pick-up strategy motivates the willingness or will to carry out activities toward positive family dental health actions. Community service aims to empower family independence through dental care innovations in improving dental hygiene status in Banda Aceh City. This community service is carried out with a descriptive method, with the target of children and their mothers as respondents. Data analysis used univariate analysis. The intervention provided was in the form of problem-based counseling, measuring the dental hygiene status of children, and demonstration of dental procedures. The result of community service is that there is an increase in knowledge, attitudes, and practices of mothers (pre-test, post-test I, post-test II) in maintaining oral and dental health with the application of dental care. There is a change towards a better dental and oral hygiene status of children with the application of dental care from pre-test, post-test I, and post-test II. It is recommended the public health services make a UKGM program using a dental nursing care pattern with home visit services in improving the dental and oral health of the family.